Three-year results of a modified photodynamic therapy procedure (Ironing PDT) for age-related macular degeneration patients with large lesions - Otsuji T (Dove Medical Press, 2016)
Tsuyoshi Otsuji,1 Kenichiro Sho,2 Akiko Tsumura,1 Naoko Koike,1 Tetsuya Nishimura,1 Kanji Takahashi2 1Department of Ophthalmology, Kansai Medical University, Takii Hospital, 2Department of Ophthalmology, Kansai Medical University, Hirakata Hospital, Osaka, Japan Background: To evaluate the effect of photodynamic therapy (PDT) using a modified procedure on exudative age-related macular degeneration having been conventionally difficult to treat.  Methods: The medical records of eight consecutive patients (eight eyes) with age-related macular degeneration treated with modified PDT were reviewed retrospectively. Modified PDT was used for the lesions that could not be covered by conventional use of PDT, either because the lesion was too large or too close to the optic disc. A moving PDT laser spot at constant speed, for 83 seconds, was used to cover the entire lesion, and was named “Ironing PDT.” This retrospective study was performed with informed patient consent. It was approved by the Institutional Review Board of Kansai Medical University.Results: No exudation could be found 36 months after treatment in five eyes (62.5%). There was no significant difference between the best-corrected visual acuity before PDT (0.95 logMAR) and after PDT (1.09 logMAR). The logMAR best-corrected visual acuity was improved in one eye, maintained in five eyes, and deteriorated in two eyes.  Conclusion: Ironing PDT decreased subfoveal fluid and preserved visual acuity in some patients with age-related macular degeneration difficult to treat with conventional therapy. Keywords: AMD, PCV, PDT, Ironing PDT, modified PDT, large lesions